Participatory simulation to foster social learning on coastal flooding prevention. (December 2017) - Becu, Nicolas; Amalric, Marion; Anselme, Brice; Beck, Elise; Bertin, Xavier; Delay, Etienne; Long, Nathalie; Marilleau, Nicolas; Pignon-Mussaud, Cécilia; Rousseaux, Frédéric
Abstract: Due to the increase in coastal flooding risk associated with sea-level rise and increasing population along the coasts, there is a strong need to develop efficient and long-term management strategies. In partnership with the local administration of Oléron Island in France, a participatory simulation model was developed to foster social learning about coastal risk prevention measures with local authorities and managers. This simulation integrates a coastal flooding model and a spatially explicit agent-based model that simulates the development of the area and the management of prevention measures. The participatory set-up includes an immersive environment for participants to remember the coastal flooding simulation displayed and a role game mechanism that simulates the coordination issues between the different decision bodies involved in coastal risk management. A first application proved that participants learn about the water expansion dynamics during flood events and the effects of building, raising and restoring dikes. Highlights: A participatory simulation tool to increase risk managers' awareness is proposed. Participatory set-up includes an immersive flooding simulation and a role game. Coastal flooding simulation computed in 4 min allowing experiential learning. Simulation allows testing coastline protection or strategic withdrawal strategy.